Communicating with parents of an ill child – a continuous challenge for a modern pediatric nurse - Wojnar, Anna (Nursing Problems / Problemy Pielęgniarstwa, 2018)
Interpersonal communication is the basis of activities undertaken by the nurse on behalf of the patient. Communication by the nurse while caring for the hospitalized child is continuously becoming more important. The pediatric nurse gains data necessary for planning and performing nursing care chiefly from the parents of the ill child. Bilateral, appropriate communication between the nurse and the parents of the pediatric patient helps both the parents and the child to get adjusted to the disease and to combat it. The continuous presence of the parents at the bedside of the child-patient is necessary, but at the same time presents the contemporary pediatric nurse with new challenges. The objective of the paper is drawing attention to the role that is fulfilled by the parent-nurse communication in the therapeutic process and to the associated challenges faced by the contemporary pediatric nurse. The paper reviews medical literature addressing the effect of the parental presence with the child in a pediatric ward. The analysis has been performed of the expectations of the parents of the hospitalized children with respect to the medical staff, as well as of the benefits and difficulties associated with the constant presence of the parents in the ward as evaluated by the pediatric nurses. Constant parental presence in pediatric hospitals seems to continue to be a novelty that is not fully accepted by the nurses. Nevertheless, a change in forming the collaboration between the parents and medical staff of pediatric wards becomes visible. Of significance is the participation of the parents in nursing and diagnostic procedures that would be adjusted to their expectations and abilities. One may note that the process of including the parents in active participation in the care of their child evolves in the right direction; nevertheless, both the parents and the staff need to learn various forms of collaboration. There is a need of improving interpersonal communication in the parents-nurse relationship, since respectfulness and personal culture in their mutual relations leave much to be desired. The prerequisite of developing the appropriate parents-nurse relation is continuous education of the nursing staff and the entire medical personnel, formulation of clear and unambiguous rules governing the parental presence in the hospital, developing appropriate standards of care that would take into consideration the role of the parent in the therapeutic team, as well as preparing appropriate hospital infrastructure.